The Role of Islamic Education in Building Moral and Spiritual Awareness in the Digital Era - Aliyatussyarifah, Siti Rahma; Khoirunisa, Siti; Maryam, Siti; Sari, Sufina (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study aims to examine the role of Islamic Religious Education (PAI) in enhancing students’ moral and spiritual awareness in the digital era. The research was driven by the increasing moral degradation and ethical challenges resulting from the uncontrolled use of technology. Islamic education, through the learning of aqidah, ibadah, akhlak, and social ethics, is expected to develop moral integrity and strengthen spiritual values among students in navigating digital challenges. Using a qualitative descriptive method, this study employed semi-structured interviews with fifty students from the Islamic Religious Education Department at UIN Sultan Maulana Hasanuddin Banten, selected purposively based on their relevance to the research topic. The findings showed that akhlak was the most influential aspect in shaping students’ moral awareness (42%), followed by aqidah (28%), ibadah (18%), and social ethics (12%). Akhlak education helps students cultivate honesty, self-control, and digital ethics, while aqidah fosters awareness of divine accountability. Furthermore, ibadah develops discipline and sincerity, and social ethics promotes fairness and social responsibility in online interactions. Overall, Islamic Religious Education plays an essential role in integrating moral and spiritual values into students’ digital behavior, fostering ethical, responsible, and faith-based digital citizens in line with the Sustainable Development Goals (SDGs).